Demographic characteristics of elite Kenyan endurance runners - Onywera, V. O.; Scott, R. A.; Boit, M. K.; Pitsiladis, Y. P. (Journal of Sports Sciences, 2006)
Kenyan athletes have dominated international distance running in recent years. Explanations for their success include favourable physiological characteristics, which could include favourable genetic endowment, and advantageous environmental conditions. The aim of this study was to compare the demographic characteristics of elite Kenyan runners with those of the general Kenyan population. Questionnaires, administered to 404 elite Kenyan runners specializing in distances ranging from the 800m to the marathon and 87 Kenyan controls, obtained information on place of birth, language, and distance and method of travel to school. Athletes were separated into two groups according to athletic success: those who competed in international competition and those who competed in national competition. The athletes differed from controls in regional distribution, language, and distance and method of travel to school; athletes also differed from each other with the exception of method of travel to school. Most national and international athletes came from the Rift Valley province (controls 20%, national athletes 65%, international athletes 81%), belonged to the Kalenjin ethnic group (controls 8%, national athletes 49%, international athletes 76%) and Nandi sub-tribe (controls 5%, national athletes 25%, international athletes 44%), and spoke languages of Nilotic origin (controls 21%, national athletes 60%, international athletes 79%). A higher proportion of all athletes ran to school each day (controls 22%, national athletes 73%, international athletes 81%) and covered greater distances. In conclusion, Kenyan runners are from a distinctive environmental background in terms of geographical distribution, ethnicity and travelled further to school, mostly by running. These findings highlight the importance of environmental and social factors in the success of Kenyan runners.